2013
DOI: 10.1093/nar/gkt1263
|View full text |Cite
|
Sign up to set email alerts
|

Human RECQ5 helicase promotes repair of DNA double-strand breaks by synthesis-dependent strand annealing

Abstract: Most mitotic homologous recombination (HR) events proceed via a synthesis-dependent strand annealing mechanism to avoid crossing over, which may give rise to chromosomal rearrangements and loss of heterozygosity. The molecular mechanisms controlling HR sub-pathway choice are poorly understood. Here, we show that human RECQ5, a DNA helicase that can disrupt RAD51 nucleoprotein filaments, promotes formation of non-crossover products during DNA double-strand break-induced HR and counteracts the inhibitory effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 59 publications
(79 reference statements)
13
55
0
1
Order By: Relevance
“…This shows that, other than PARylation, phosphorylation also regulates the recruitment of RECQL5 and WRN at sites of double-strand breaks. Previously, it was reported that RECQL5 enhances noncrossover HR-mediated DSB repair (30). Indeed, our results support this finding and furthermore show that RECQL5 and PARP1 participate in the same pathway (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This shows that, other than PARylation, phosphorylation also regulates the recruitment of RECQL5 and WRN at sites of double-strand breaks. Previously, it was reported that RECQL5 enhances noncrossover HR-mediated DSB repair (30). Indeed, our results support this finding and furthermore show that RECQL5 and PARP1 participate in the same pathway (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that RECQL5 interacts with RAD51 to inhibit RAD51-induced D-loop formation and sister chromatid exchange (29). Consistent with that finding, RECQL5 prevents RAD51 single-stranded DNA (ssDNA) filament formation by promoting synthesis-dependent strand annealing to mediate DSB repair (30). Our previous studies used confocal laser microscopy to study the kinetics of recruitment of RECQL5 to DSBs in real time in live cells (31).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Interestingly, both yeast Srs2 and mammalian RECQ5 have been implicated in antirecombination (see above) and anticrossover pathways (Aylon et al 2003;Ira et al 2003;Paliwal et al 2014). Although the mechanisms involved still need to be established, it is possible that removal of Rad51 from ssDNA is involved in both.…”
Section: Reversibility Of Extended D-loops: a Step In Sdsa And A Mechmentioning
confidence: 99%
“…Human BLM, along with TopIII α topoisomerase, promotes noncrossover formation by dissolution of dHJ intermediates and by preventing the exchange of flanking sequences (Wu and Hickson 2003). Recently, another member of the RecQ helicase family, RecQ5, a potential Srs2 ortholog in mammals, was shown to promote SDSA by disrupting Rad51-ssDNA filaments and counteracting the inhibitory effect of Rad51 on the strand-annealing activity of Rad52 (Paliwal et al 2014). It will be interesting to examine whether FANCM can also perform a function similar to its yeast ortholog, Mph1, in dissociating Rad51-coated D loops and promoting SDSA.…”
Section: Sdsamentioning
confidence: 99%